Ureaplasma in pregnancy. Is there any risk for preterm labor? - Hristiana CAPROS (One Health & Risk Management)
Introduction. Ureaplasma species, particularly Ureaplasma urealyticum and Ureaplasma parvum, inhabit the lower genital tract of sexually active women and have been linked to adverse reproductive outcomes. This review highlights their role in pre-term delivery, along with detection challenges and pathogenic mechanisms. Material and methods. This review compiles data from 25 studies, encompassing a total of approximately 15,700 patients. These studies include retrospective and prospective cohorts, cross-sectional designs, and case-control studies. Key parameters evaluated included the impact of Ureaplasma species on pregnancy outcomes, such as preterm labor and chorioamnionitis. Results. The studies reviewed (2000–2024) included 10 retrospective, 8 prospective, 4 cross-sectional, and 3 case-control designs. Ureaplasma parvum was found in 40.5% of healthy women and Ureaplasma urealyticum in 20.3%. Intra-amniotic infection increased preterm delivery risk (OR: 2.76–3.0), with preterm birth rates ranging from 26% to 58.6%. Ureaplasma induces pro-inflammatory cytokines, activates neutrophils and TLR-9, and increases prostaglandin and matrix metalloproteinase activity, weakening fetal membranes and triggering preterm labor. Conclusions. Ureaplasma spp. significantly contribute to preterm delivery, primarily through inflammatory processes and membrane damage. Further research with prospective randomized studies is recommended.